PERAN KEPEMIMPINAN LURAH DALAM PEMBERDAYAAN MASYARAKAT DI KELURAHAN MAHARATU KECAMATAN MARPOYAN - Ramadhan Pratama; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Community empowerment is basically a process to make people become empowered. Every member of the community in a community actually has the potential, the ideas and the ability to bring himself and his community to go to a better direction, but the potential it sometimes can not advance due to certain factors. To move back to self-reliance in development in their communities, it is necessary impulses or early ideas for reviving the role and position within the framework to build a civil society. Public awareness-raising process is conducted through the concepts of capacity building. Community capacity development is a form of efforts to develop the knowledge, attitudes and skills of the community to participate actively in carrying out independent and sustainable development.Community empowerment is done through active participation is facilitated by the presence of the empowerment drive. Empowerment mover is one who has the power or authority in an organization or region. Pengerak it will only be effectively done by a leader. The primary role of a leader is able to influence others to voluntarily achieve the targets that have been set. Leaders set goals and inspire others to achieve these goals.Urban Village is a governmental organization located on the frontline in the city administration. Thus governmental organizations village as an institution leader in charge of development, in line with the objectives of independence and hopes of our founding fathers prioritize how government institutions currently able to carry out wheel central and local governments properly and capable hand in hand in increasing progress and accelerated development in Indonesia for the function of the village is able to provide administrative services to the community and the importance of government objectives in terms of ideology, political, social, economic, and security. everything that comes from human beings who run, because it pembanggunan of by and for the people means the man himself.Based on the research that has been done, based on the data analysis process it has been known that empowerment in the Village District of Marpoyan Damai Maharatu run very well. It's just that there are some things that become an obstacle thatcommunication should be better in the interlace as head headman in the village to the community.